Ekofeminisme Spritiualis pada Gerakan Perempuan Adat dalam Menolak Tambang Marmer di Mollo, Nusa Tenggara Timur - Cindy Parastasia (Pustaka Peradaban, 2024)
The article aims to elaborate on the spiritual ecofeminist movement in the effort to resist mining by indigenous women of Mollo, East Nusa Tenggara. The environmental protection movement led by Mollo women demonstrates the equality of women and nature. This equal position is manifested through resistance movements to protect the environment from mining companies (capital) attempting to dominate the Mollo, South Central Timor, East Nusa Tenggara region. The research method used in this study is descriptive analytical, referring to the analysis model by B. Miles and Michael Huberman. The environmental damage caused by capitalist-style extractive exploitation also negatively impacts women, highlighting the dominance of masculinity over femininity in the Mollo region. The equal position between women and nature and their close relationship provide reasons to initiate a resistance movement. The resistance movement led by indigenous Mollo women is one representation of the Spiritual Ecofeminist movement in Indonesia that responds to and rejects environmental exploitation. The principles believed by Mollo women reflect the thoughts of Spiritual Ecofeminism and serve as the foundation for the movement against marble mining. These principles involve earth-based spiritual practices and the concept of interconnectedness between mind, body, and nature. Tulisan ini bertujuan untuk mengelaborasi gerakan ekofeminisme spiritual dalam upaya menolak tambang oleh perempuan adat Mollo, Nusa Tenggara Timir. Gerakan perlindungan lingkungan yang dilakukan para perempuan Mollo menunjukkan bahwa posisi perempuan dan alam adalah setara. Posisi yang setara ini ditunjukkan melalui gerakan perlawanan dalam melindungi lingkungan dari perusahaan tambang (kapital) yang berupaya mendominasi alam Mollo, Timor Tengah Selatan, NTT. Metode penelitian yang digunakan penelitian ini adalah deskriptif analitik dengan mengacu pada model analisis B. Miles dan Michael Huberman. Dampak kerusakan pada alam yang diakibatkan oleh eksploitasi eksktraktif ala kapitalisme juga berdampak negatif pada perempuan, dan memperlihatkan dominasi maskulinitas atas femininitas di wilayah Mollo. Posisi setara antara perempuan dan alam serta hubungan eratnya menjadi alasan untuk memulai gerakan perlawanan. Gerakan perlawanan yang dilakukan para perempuan adat Mollo menjadi salah satu representasi gerakan Ekofeminisme Spiritualis di Indonesia yang merespons dan menolak eksploitasi alam. Prinsip-prinsip yang diyakini perempuan Mollo mencerminkan pemikiran Ekofeminisme Spiritualis dan dijadikan landasan gerakan untuk menolak tambang marmer. Prinsip tersebut berupa praktik spiritualitas berbasis bumi dan adanya konsep keterhubungan pikiran, tubuh, dan alam.